Chickenpox in Children: Features of Treatment - S.A. Kramarev; O.V. Vygovskaya; V.V. Deyev; A.P. Moshich; O.F. Melnikov; A.V. Shashkina; Yu.Ye. Nadvorskaya; O.S. Pilipenko; T.A. Kolinko; U. Godvin (Zaslavsky O.Yu., 2014)
We observed 96 children with chickenpox aged from 2 weeks to 17 years. These patients had violations of interferon and cytokine status. Inclusion of Laferobionum into complex of treatment for chickenpox in children contributes to a more rapid involution of the main symptoms of the disease, normalizes initially altered level of interferon gamma and levels of major cytokines - interleukin-2, -4, -6, -8, -10 and tumor necrosis factor alpha.